The Relationship Between Peers and Learning Interest of Citizens Learning the Package C Program at SPNF SKB Sijunjung - Anggun Maita Rusadi; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research was motivated by the low interest in learning of the members of learning the package C program at SPNF SKB Sijunjung, this is thought to be due to the negative influence exerted by peers. This study aims to: 1) describe peer influence; 2) describe the learning interest of the learning community; and 3) looking at the relationship between peer influence and the learning interest of citizens in the Paket C program at SPNF SKB Sijunjung. This type of research is quantitative research with correlational descriptive techniques. The population of this research is all citizens studying the Paket C Program at SPNF SKB Sijunjung totaling 19 people and all of them are used as research samples. The data collection technique is in the form of a questionnaire with the data collection tool in the form of a questionnaire. The data analysis technique used the percentage formula and Spearman rho correlation. The results showed that: (1) peer influence was categorized as bad, (2) learning interest in learning citizens was categorized as low, (3) there was a significant relationship between peer influence and learning interest in learning citizens in the package C program at SPNF SKB Sijunjung. It is recommended that tutors be able to provide knowledge and help generate interest in learning with the support of peers, and for learning citizens so that they can have a good influence on their peers.This research was motivated by the low interest in learning of the members of learning the package C program at SPNF SKB Sijunjung, this is thought to be due to the negative influence exerted by peers. This study aims to: 1) describe peer influence; 2) describe the learning interest of the learning community; and 3) looking at the relationship between peer influence and the learning interest of citizens in the Paket C program at SPNF SKB Sijunjung. This type of research is quantitative research with correlational descriptive techniques. The population of this research is all citizens studying the Paket C Program at SPNF SKB Sijunjung totaling 19 people and all of them are used as research samples. The data collection technique is in the form of a questionnaire with the data collection tool in the form of a questionnaire. The data analysis technique used the percentage formula and Spearman rho correlation. The results showed that: (1) peer influence was categorized as bad, (2) learning interest in learning citizens was categorized as low, (3) there was a significant relationship between peer influence and learning interest in learning citizens in the package C program at SPNF SKB Sijunjung. It is recommended that tutors be able to provide knowledge and help generate interest in learning with the support of peers, and for learning citizens so that they can have a good influence on their peers.Keywords: Peers, Interest in learning, Program Package C